Division into narcotic drugs, psychotropic substances and their precursors in international and national law - Kharevich, Dmitry L. (Journal of the Belarusian State University. Law, 2024)
The problem of division of controlled substances into narcotic drugs, psychotropic substances and their precursors is studied. Public relations in the sphere of circulation of these substances are researched, the norms of the UN anti-drug conventions and legislative acts of the Republic of Belarus regulating them are analysed. Patterns of species identification of psychoactive substances under control, which made it possible to reconsider some views on this issue are identified. The purpose of the study is to improve the conceptual apparatus in the field of drug control. The practical significance of its results is to substantiate changes in the legislation regulating drug trafficking, allowing to optimise the legal terminology in this area.